Electrochemical Behaviour of Lithium, Sodium and Potassium Ion Electrolytes in a Na0.33V2O5 Symmetric Pseudocapacitor with High Performance and High Cyclic Stability. Issue 1 (2nd November 2017) - Manikandan, Ramu; Raj, C. Justin; Rajesh, Murugesan; Kim, Byung Chul; Sim, Ju Yong; Yu, Kook Hyun
Abstract: A high‐performance symmetric supercapacitor was fabricated using a Na0.33 V2 O5 nanocomposite synthesized by means of a simple co‐precipitation technique. The structural and morphological investigation showed that the synthesized Na0.33 V2 O5 nanocomposite exhibited a monoclinic structure with a nanorod‐like morphology. The electrochemical properties of the Na0.33 V2 O5 symmetric supercapacitor were studied utilizing three different aqueous electrolytes, such as 1 M of LiCl, NaCl and KCl, respectively. Interestingly, the fabricated Na0.33 V2 O5 symmetric supercapacitors exhibited excellent electrochemical capacitance behaviour in all the electrolytes with a maximum specific capacitance value of 168 F g −1 in 1 M LiCl, 146 F g −1 in 1 M NaCl and 132 F g −1 in 1 M KCl electrolytes at 0.5 A g −1 discharge current density. In addition, Na0.33 V2 O5 symmetric supercapacitors demonstrated an excellent cyclic stability in 1 M NaCl electrolyte with high capacitance retention of approximately 81 % after 50 000 charge/discharge cycles. Abstract : On balance : A symmetric supercapacitor was fabricated utilizing Na0.33 V2 O5 nanorods and its performance was studied in Li +, Na + and K + cation based aqueous electrolytes. The Na0.33 V2 O5 symmetric supercapacitor showed better electrochemical performance with excellent cyclic stability for 50 000 charge/discharge cycles in all three electrolytes.